Menjawab Kebijakan Pemerintah Mengenai Perkembangan Dunia Tentang Pendidikan Inklusi - Kalbu Patma Wati; Silvia Indriani; Agustomi Agustomi; Opi Andriani (Institut Nalanda, 2024)
The aim of this research is to find out government policies regarding world developments regarding inclusive education. The method used in this research is a literature review study or literature review. Literature study is a research design used to collect data sources related to a topic found in the field. Data collection uses literature studies from several national journals found. The results of this research are that the success of implementing inclusive education will depend on the collaboration of the government, teachers and parents together.